The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.17516/1998-2836-0132
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Zr-Bearing Sorption Materials Based on Coal Fly Ash Microspheres

Abstract: The influence of hydrothermal conditions on synthesis of analcime and a composite material ZrO2- analcime as well as zirconomolybdate coverings with ion exchange properties was studied using narrow fractions of aluminosilicate microspheres with a high content of a glass phase (91-95 wt. %). The possibility to synthesize ZrO2-analcime composites of narrow particle size distributions with maximum of about 40 μm and 6 μm under hydrothermal treatment at 150 °С was demonstrated starting from microspheres with Si/Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Evaluation of sorption properties of the small-sized HZD-ANA particles with respect to Nd 3+ , taken as an imitator of actinides (III), demonstrated that the material traps Nd 3+ cations from diluted solutions with a distribution coefficient of about 10 5 mL/g and efficiency of up to 99.6% [22]. The Nd 3+ sorption parameters obtained for HZD-ANA are comparable with ones determined for pure analcime.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Evaluation of sorption properties of the small-sized HZD-ANA particles with respect to Nd 3+ , taken as an imitator of actinides (III), demonstrated that the material traps Nd 3+ cations from diluted solutions with a distribution coefficient of about 10 5 mL/g and efficiency of up to 99.6% [22]. The Nd 3+ sorption parameters obtained for HZD-ANA are comparable with ones determined for pure analcime.…”
Section: Introductionsupporting
confidence: 56%
“…The size of pore entrances imparts a molecular/ion sieve property to zeolites. In particular, analcime (ANA) having the minimal pore entrances (d = 2.6 Å) compared to other zeolites displays an affinity towards well-proportioned cations of actinides, lanthanides, and heavy metals [20][21][22]. At the same time, due to the ion sieving effect, analcime has a poor Cs + and Sr 2+ sorption capacity at 25 °C [23] but is capable to trap these cations under hydrothermal conditions at 250-300 °C [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation